نطاق حجية أحكام المحكمة الجنائية الدولية - ضاحي, نايف احمد (Journal of Legal Sciences, 2017)
We had, in this research, the scope of Authentic provisions of the International Criminal Court, where divided by the two sections: the first, outlining the concept of Authentic provisions of the International Criminal Court, as we dealt with the definition in the Authentic res judicata where the conditions matter, and the scope of Authentic provisions of the International Criminal Court in terms of the parties and time and place.The second section, we have considered the appeal against the provisions of the International Criminal Court, where we explained the challenge the provisions of the International Criminal Court to appeal and cassation, as well as the revision of the provisions of the International Criminal Court.In conclusion we explained the most important conclusions we reached in this regard, and some of the necessary recommendations in this area.